The relationship between post‐traumatic stress and post‐traumatic growth in cancer patients and survivors: A systematic review and meta‐analysis. Issue 4 (14th January 2020) - Marziliano, Allison; Tuman, Malwina; Moyer, Anne
Abstract: Objective: Research on the relationship between post‐traumatic stress disorder (PTSD)/post‐traumatic stress symptoms (PTSS) and post‐traumatic growth (PTG) in cancer patients and survivors is increasing. Methods: We conducted a systematic review and meta‐analysis of 51 studies that assessed the relationship between PTSD/PTSS and PTG, in cancer patients/survivors. Five databases were searched through 29 April 2019. The purpose of this manuscript is to report a summary of this literature, the aggregate effect size of the relationship between PTSD and PTG, and the examination of potential moderators that may impact the relationship between PTSD and PTG. Results: The aggregate weighted effect size for the association between PTSD/PTSS and PTG was small, r = .08, but significantly different from zero. We examined whether time since diagnosis, stage of cancer, type of measure used to assess PTSD/PTSS, or type of measure used to assess PTG explained the significant heterogeneity among the individual effect sizes. The relationship was significantly stronger for the small subset of studies that included only stage 4 patients compared with those that included only non–stage 4 patients. Additionally, the strongest relationship was for those studies that used the Impact of Events Scale‐Revised to assess PTSD. Conclusions: The relationship between PTSD/PTSD and PTG is modestly positive and robust. There is evidence that the threat of advanced cancer is more strongly associated with growth, but none supporting that more time since cancer diagnosis allows survivors the opportunity to positively reinterpret and find meaning in the traumatic aspects of the disease resulting in more growth.